Silence after narratives by patients in psychodynamic psychotherapy: a conversation analytic study - Carolina Fenner (Frontiers in Psychology)
In psychotherapy, verbal communication is central to the therapeutic process. However, when patients remain silent, it can serve various functions, such as reflecting more deeply or hesitating to elaborate on a topic. This article uses conversation analysis to examine a specific context in which silence occurs: After a patient has concluded his/her narrative, both the therapist and the patient resist the turn allocation by the respective other, resulting in mutual silence. The results indicate that both therapists and patients collaboratively generate this silence. Therapists typically end the silence with an intervention, addressing an aspect of the topic and treating the pause as intra-topic silence. The study is based on approximately 29 h of video recordings of German-speaking outpatient psychodynamic psychotherapy sessions. This research highlights the importance of therapists recognizing the different forms of silence that may emerge during psychotherapy.